1

I want to write down this equation in latex.

\bar\Omega_t=\bar\Sigma_t^{-1}
             =[G_t\Sigma_{t-1}G_t^T+F_x^TR_t^xF_x]

The code I write down in latex to display this equation is

\begin{equation}
\bar\Omega_t=\bar\Sigma_t^{-1}
            =[G_t\Sigma_{t-1}G_t^T+F_x^TR_t^xF_x]
 \end{equation}

It throws error. Also I want a line by line output meaning \bar\Omega_t=\bar\Sigma_t^{-1} equation line no: 1 and =[G_t\Sigma_{t-1}G_t^T+F_x^TR_t^xF_x] equation lin no: 2. How could I do that?

1

I thing useing align from amsmath package would be better.

\documentclass{article}
\usepackage{amsmath}
\begin{document}
\begin{align}
  \bar\Omega_t&=\bar\Sigma_t^{-1}\\
              &=[G_t\Sigma_{t-1}G_t^T+F_x^TR_t^xF_x]
\end{align}
\end{document}
6

it is not clear what is your problem. see if any of following example is what you like to obtain:

enter image description here

\documentclass{article}
\usepackage{amsmath}

\begin{document}
\begin{equation}
\bar\Omega_t = \bar\Sigma_t^{-1}
             = [G_t\Sigma_{t-1}G_t^T+F_x^TR_t^xF_x]
 \end{equation}

\begin{equation}
\begin{split}
\bar\Omega_t & = \bar\Sigma_t^{-1}   \\
             & = [G_t\Sigma_{t-1}G_t^T+F_x^TR_t^xF_x]
\end{split}
 \end{equation}

\begin{align}
\bar\Omega_t & = \bar\Sigma_t^{-1} \\
             & = [G_t\Sigma_{t-1}G_t^T+F_x^TR_t^xF_x]
 \end{align}
 \end{document}

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.